Mediterranean Tourism policy and the socioeconomic impacts in the Mediterranean countries (especially) after the Arab Spring-the case of Tunisia - Κωνσταντάρα, Δήμητρα (Πανεπιστήμιο Πελοποννήσου, 2017)
The aim of the research of the current dissertation is to describe the trends of Mediterranean Tourism policy and specify the socioeconomic impacts on Mediterranean countries after the outbreak of the Arab spring, focusing on the case of Tunisia where the Arab Spring‟s movement had started. Examining the impacts in the economy of the country, mainly in society and also the potential for facing youth unemployment which is the most painful issue for the economies, especially in the MENA region. In the first chapters, there will be an attempt to present some useful information around Tourism and give the background situation before the Arab Spring regarding tourism policy in the Mediterranean region. In the following chapters, there will be an effort of mapping the situation of Tourism in South Eastern Mediterranean countries (not only EU countries), before and after the Arab Spring and its repercussions to the countries. (Loss of Tourism, reduction of arrivals, fear of Jihadist attacks, insecurity, trends). To conclude, there are some considerations regarding Tourism policy activating institutional tools as well as some proposals for restoring the familiarization of the Westerns with the South East Mediterranean, as a preferable exotic tourist destination.
Μεσογειακή τουριστική πολιτική και κοινωνικοοικονομικές επιδράσεις στις χώρες της Μεσογείου (ειδικά) μετά την Αραβική Άνοιξη: η περίπωση της Τυνησίας
Keywords: Τουρισμός; Οικονομική ανάπτυξη; Μεσόγειος, Περιοχή της; Μεσογειακές Χώρες; Τουρισμός; Αραβική Άνοιξη; Ασφάλεια; Τυνησία